Magnetospheric Multiscale Mission observations and non‐force free modeling of a flux transfer event immersed in a super‐Alfvénic flow. Issue 12 (30th June 2016) - Farrugia, C. J.; Lavraud, B.; Torbert, R. B.; Argall, M.; Kacem, I.; Yu, W.; Alm, L.; Burch, J.; Russell, C. T.; Shuster, J.; Dorelli, J.; Eastwood, J. P.; et al.
Abstract: We analyze plasma, magnetic field, and electric field data for a flux transfer event (FTE) to highlight improvements in our understanding of these transient reconnection signatures resulting from high‐resolution data. The ∼20 s long, reverse FTE, which occurred south of the geomagnetic equator near dusk, was immersed in super‐Alfvénic flow. The field line twist is illustrated by the behavior of flows parallel/perpendicular to the magnetic field. Four‐spacecraft timing and energetic particle pitch angle anisotropies indicate a flux rope (FR) connected to the Northern Hemisphere and moving southeast. The flow forces evidently overcame the magnetic tension. The high‐speed flows inside the FR were different from those outside. The external flows were perpendicular to the field as expected for draping of the external field around the FR. Modeling the FR analytically, we adopt a non‐force free approach since the current perpendicular to the field is nonzero. It reproduces many features of the observations. Key Points: Draping signatures around an FTE Non‐force free modeling of the FTE flux rope Detailed plasma behavior in and around FTE